The new Naira notes redesign as drivers of the performance of small and medium scale enterprises in Nigeria - James, Ighoroje Ese; Agbarha, Egberi Kelvin; Emmanuel, Akpokerere Othuke (International Journal of Management and Sustainability, 2024)
The study analyzed whether the Naira note redesign matters for the performance of small and medium-scale enterprises in Nigeria. The study sought to examine (1) effect of the Naira note redesign on the performance of small and medium-scale enterprises; (2) effect of circulation of the new Naira notes on the performance of small and medium scale enterprises; (3) effect of Naira scarcity on the performance of small and-medium scale enterprises. The survey design was used, and questionnaire was administered to three hundred forty-seven (347) small and medium-scale enterprises in the south-east of Nigeria. Data obtained were analyzed using descriptive statistics (simple percentages, frequency count, mean, standard deviation, kurtosis, skewness, Pearson correlation) and inferential statistics (multiple regression). Findings showed that Naira note redesign has a significant negative effect on the performance of small and medium-scale enterprises. In addition, it was shown that the circulation and scarcity of the new naira notes had a significant effect on the performance of small and medium-scale enterprises in Nigeria. The study recommends that the government should implement currency revaluation and single exchange rate regime, as these would help in stabilizing exchange rates, and reduce uncertainties linked to small and medium-scale enterprises, improve competitiveness, and boost their confidence. Also, governments at all levels should invest in infrastructure, digital training, and enabling regulatory environments to encourage small and medium-scale enterprises to incorporate digital transformations and resilience in their operations, as it would enhance growth and development of small and medium-scale enterprises.